KARAKTERISASI TOKOH DALAM ROMAN DER FÜRST SPRICHT KARYA JAN PETER BREMER - DAMAYANTI, WINDI (UNIVERSITAS NEGERI SURABAYA, 2016)
Literature is a form of creativity idea from the author. One of the forms is roman. There are characters in a roman. In the source of the data which was used is written data of Der Fürst spricht roman by Jan Peter. In this research selected roman Der Fürst spricht of Jan Peter Bremer as research objects. Roman Der Fürst spricht tells about der Fürst and his servants, if it is associated with a sense of romance, there is also the linkages between der Fürst and his servants. Therefore, need to know these linkages to understand the story well. Then, there are figures in a roman. For making the figures live, the author needs the characterization.. According to Minderop, characterization is character description. The research question of this research is: How the characterization of the characters in Der Fürst spricht roman by Jan Peter Bremer?. The purpose of this research is finding the characterization of the figures in Der Fürst spricht roman by Jan Peter Bremer. This research included into descriptive qualitative research. For analyzing the research problem, the research used a theory about indirectly characterization from Albertine Minderop and Enneagram theory from Oscar Ichazo dan Claudio Naranjo . The result of analysis showed that the roman of Der Fürst spricht by Jan Peter Bremer had, 1 figure tempered leader, 1 figure tempered wicked, 1 figure tempered liar, 3 characters tempered friendly, 1 figure tempered rescuer, 1 figure tempered romantic, 1 figure tempered generalist, 3 figures tempered faithful, 1 figure tempered careful, and 1 figure cruel character. Once found the character it can be seen that in the roman Der Fürst spricht more inclined to depictions through sociological terms, because the author depicts characters through figures interaction in the environment. Where all the figures in the roman Der Fürst spricht interact with each other in environment so it appears the character of each figure. Keywords : Roman, characterization,  figure.